Ethiopia Public Expenditure Review : The Emerging Challenge, Volume 1. Public Spending in the Social Sectors 2000-2020 - World Bank (Washington, DC, 2013)
This Public Expenditure Review (PER) features the expenditure requirements confronting the government which are enormous; and, the expenditure requirements confronting Ethiopia which are compounded by rapid population growth. The expenditure consequences are significant, because social programs are intensive in their demands on recurrent resources, so the expansions being committed to today, could overwhelm budget obligations in 20 years time, crowding out the capacity to fund other investments for growth. Furthermore, because of the very limited capacity to finance these needs domestically, they will heavily influence foreign aid requirements over the next two decades. Finally, because the cost of these programs fall primarily on the regional and local governments, they imply the need for a major increase in the share of resources transferred to lower level governments. The object of this PER is to put the numbers on the table to inform this debate. Current spending on education, health, population, food security transfers, and water supply is examined, along with an assessment of its adequacy, effectiveness, and absorptive capacity. The PER then projects the costs of alternative coverage targets over the next 20 years, including the costs of reaching the Millennium Development Goals (MDGs), and examines the implications for financing, and sectoral policy choices. Three cost scenarios are forecast for each sector: a 'business-as-usual' scenario that shows the cost of just keeping up with population growth; an 'Extended (Poverty Reduction Strategy Paper ) PRSP' scenario, that projects the costs of continuing with moderately ambitious targets developed over the past few years; and, finally an 'MDGs Plus' scenario that forecasts the full costs of implementing the most ambitious plans that government is currently proposing in various policy documents. The report comprises two volumes: public spending in the social sectors 2000-2020 (V. 1), and, medium trends and recent developments in public spending (v. 2), that includes statistical annexes.